First record of Urotrema scabridum (Platyhelminthes), and new records of helminths of Tadarida brasiliensis from Mexican Plateau - Martínez-Salazar, Elizabeth A.; Medina-Rodríguez, Andrea J.; Rosas-Valdez, Rogelio; Del Real-Monroy, Melina; Falcón-Ordaz, Jorge (THERYA, 2020)
The Mexican free-tailed bat (Tadarida brasiliensis) is an abundant, widely distributed species in Mexico, except for most of the Yucatán peninsula. We studied the helminth fauna of T. b. mexicana at seven localities in the State of Zacatecas in order to advance the knowledge of helminth parasites of wild vertebrates in northern-central Mexico. Eighty-four bat specimens were examined for the presence of helminth parasites following standard procedures; helminths found were identified and infections were characterized. Of the specimens examined, 65.47 % were parasitized. The helminth fauna comprises five taxa: three digeneans (Dicrocoelium rileyi, Ochoterenatrema labda, and Urotrema scabridum); one cestode (Vampirolepis sp.); and one nematode (Tadaridanema delicatus). We present a brief morphological description of Urotrema scabridum. D. rileyi was the most prevalent and abundant helminth species. The intestine was the habitat most parasitized, with four species. Indirect life cycles predominate, and are related to the insectivorous habits of this host. Further studies on this host-parasite system are necessary to contribute to population monitoring and conservation; biogeographic patterns of helminth parasites of bats should also be studied to explore their origins and evolution in the region. U. scabridum is reported for the first time from Zacatecas. All species are new locality records.